CREATING THE WEATHER APPLICATION IN PYTHON - Malikov , Umidjon; Akhmedova, Iroda (MMIT Proceedings, 2023)
This work describes the process of creating the Weather application, which allows users to get up-to-date information about weather conditions in a specified area anywhere in the world using the integrated PyOWM shell, shows the values of temperature, temperature: "feels like", wind speed, pressure, humidity. In the process of developing the application, various technologies and tools were used, such as an API for obtaining weather data, Frameworks for developing a user-friendly interface. The Weather app is suitable for permissions on all platforms (Android, iOS, Windows, macOS, Linux), implemented both for running on a computer and via a smartphone. The application is intended for personal use, tourism, as well as in the fields of economy, agriculture, transport, construction, etc